Role of Matrix in an Early Postentry Step in the Human Immunodeficiency Virus Type 1 Life Cycle - Kiernan, Rosemary E. (American Society for Microbiology, 1998)
The matrix protein of human immunodeficiency virus type 1 (HIV-1) has been reported to play a crucial role in the targeting of the Gag polyprotein precursor to the plasma membrane and in the incorporation of viral envelope glycoproteins into budding virions. In this report, we present evidence that mutation of a highly conserved Leu at matrix amino acid 20 blocks or markedly delays virus replication in a range of cell types, including T-cell lines, primary human peripheral blood mononuclear cells, and monocyte-derived macrophages. These mutations do not impair virus assembly and release, RNA encapsidation, or envelope glycoprotein incorporation into virions but rather cause significant defects in an early step in the virus life cycle, as measured by single-cycle infectivity assays and the analysis of viral DNA synthesis early postinfection. This infectivity defect is independent of the type of envelope glycoprotein carried on mutant virions; similar results are obtained in pseudotyping experiments using wild-type or truncated HIV-1 envelope glycoproteins, the amphotropic murine leukemia virus envelope, or the vesicular stomatitis G protein. Intriguingly, matrix residue 20 mutations also increase the apparent binding of Gag to membrane, accelerate the kinetics of Gag processing, and induce defects in endogenous reverse transcriptase activity without affecting virion density or morphology. These results help elucidate the function of matrix in HIV-1 replication.